PENERAPAN SISTEM JAMINAN HALAL PADA RUMAH POTONG HEWAN (RPH) RUMINANSIA KOTA SINGKAWANG - Fitri Apriani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This research departs from the phenomenon of the application of the Halal Assurance System (SJH). Where HAS, this is a mechanism that must be applied by producers as one of the requirements for issuing Halal Certificates. One of the places that has implemented SJH and already has a Halal Certificate is the Ruminant Slaughterhouse (RPH) of Singkawang City and is a place for researchers to conduct research. The focus of this research are: 1) How is the implementation of SJH in Ruminant Slaughterhouse in Singkawang City? 2) What are the supporting and inhibiting factors in the SJH process in the Ruminant Slaughterhouse of Singkawang City? This research uses a qualitative approach and descriptive research type, data collection techniques using interview techniques, documentation and observation. This study also uses data analysis in the form of data reduction, data display, conclusions and verification as well as data validity checking techniques in the form of: 1) participation extension techniques; 2) Improve accuracy / persistence and 3) Member check. The results of the research carried out were the implementation of HAS in the Ruminant Slaughterhouse of Singkawang City referring to the 23000 Halal Assurance System (HAS). From the research carried out, it can be seen that the process of slaughtering cows, namely the incoming cows will be tested for ante mortem, the cows that come are rested, then slaughtered use a sharp knife and read basmallah. After the slaughter, decapitalization, skinning and removal of the offal will be carried out. Then a post mortem examination is carried out by the medical personnel, if the beef cattle do not have the disease, it will be distributed to consumers. Supporting factors in implementing SJH are: 1) Officers at Ruminant RPH Singkawang City are Muslims; 2) Public awareness regarding halal products is also high; 3) Availability of clean water facilities; 4) Supporting road access; 5) Consumer interest in halal cut meat is high. While the inhibiting factors are: 1) the location of the minimalist Ruminant Slaughterhouse in Singkawang City; 2) Has a very close distance to the shelter cage and restrain box; 3) the separation of dirty and clean rooms is not perfect; 4) peeling does not use a cradle; 5) workers' lack of awareness of hydene and sanitation and 6) lack of public knowledge about the meaning of halal itself.